La gestación del Transantiago en el discurso público: hacia un análisis de políticas públicas desde la perspectiva cognitivista - Antoine Maillet (Nuevo mundo - Mundos Nuevos, 2008)
This paper aims to trace the public discourse surrounding the reform of public transportation in Santiago de Chile, with the purpose of interpreting it from the cognitivist perspective in policy analisis. The representations of the actors of the reform emerge from elements of public discourse found in press articles or official documents. The use of “common places” from Chilean politics by the supporting coalition, such as development and modernization, undermines the capacity of the opposition to organize and effectively build a coalition. As a consequence, the situation can be described from the chosen perspective, the Advocacy Coalition Framework, as the constitution of a hegemonic coalition by reform supporters. This operation takes place to the detriment of the users of public transportation. The study reveals that they are absent from the representations of decision-makers, who put the emphasis on the comparison of the image of Santiago with cities from the developed world. This functionalist vision of public transportation might explain part of the problems the reform has experienced in its implementation.